Bifurcation of equilibrium forms of an elastic rod on a two-parameter Winkler foundation. (February 2018) - Izydorek, Marek; Janczewska, Joanna; Waterstraat, Nils; Zgorzelska, Anita
Abstract: We consider two-parameter bifurcation of equilibrium states of an elastic rod on a deformable foundation. Our main theorem shows that bifurcation occurs if and only if the linearization of our problem has nontrivial solutions. In fact our proof, based on the concept of the Brouwer degree, gives more, namely that from each bifurcation point there branches off a continuum of solutions.